2016
DOI: 10.1128/aac.01240-15
|View full text |Cite
|
Sign up to set email alerts
|

Gallium Potentiates the Antibacterial Effect of Gentamicin against Francisella tularensis

Abstract: The reasons why aminoglycosides are bactericidal have not been not fully elucidated, and evidence indicates that the cidal effects are at least partly dependent on iron. We demonstrate that availability of iron markedly affects the susceptibility of the facultative intracellular bacterium Francisella tularensis strain SCHU S4 to the aminoglycoside gentamicin. Specifically, the intracellular depots of iron were inversely correlated to gentamicin susceptibility, whereas the extracellular iron concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…They also found that gallium enhanced the effectiveness of gentamicin. 112 Boza et al examined the activity of a series of metalloporphyrins, including GaPP and several other gallium porphyrins, such as GaMP, and gallium hematoporphyrin (GaHPIX), against the sexually transmitted bacteria Neisseria gonorrhoeae and Haemophilus ducreyi. GaPP had an average minimal growth inhibitory concentration (MGIC) of 8 μg/mL while GaMP and GaHPIX had MGICs of 32 and 16 μg/mL, respectively.…”
Section: Acs Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that gallium enhanced the effectiveness of gentamicin. 112 Boza et al examined the activity of a series of metalloporphyrins, including GaPP and several other gallium porphyrins, such as GaMP, and gallium hematoporphyrin (GaHPIX), against the sexually transmitted bacteria Neisseria gonorrhoeae and Haemophilus ducreyi. GaPP had an average minimal growth inhibitory concentration (MGIC) of 8 μg/mL while GaMP and GaHPIX had MGICs of 32 and 16 μg/mL, respectively.…”
Section: Acs Infectious Diseasesmentioning
confidence: 99%
“…129 Lindgren and Sjostedt used a combination of gentamicin and gallium citrate to treat bone marrow-derived macrophages infected with the SCHU 4 strain of F. tularensis. 112 By using them together, the compounds exerted a much greater bactericidal effect than either compound individually, seeing a 98% inhibition of growth compared to that of the control and displaying a high degree of synergism (FICI < 0.05). When mice infected with the LVS strain of F. tularensis were treated with gentamicin (0.2 mg/mouse) and/or gallium (0.6 mg/ mouse) or a PBS control, the combination-treated mice saw a drastic reduction in the number of bacteria observed in the liver compared to both the mock and singly treated mice.…”
Section: Synergistic Effect Of Gallium Compounds With Other Antibioticsmentioning
confidence: 99%
“…After a time for incubation (18-24 h), bacterial cells are quantified either via eukaryotic cell lysis and cell plating (if possible) or a variety of other quantification methods based upon the bacterium in question. Such an assay was performed to demonstrate the synergistic activity of gallium to gentamicin against intracellular F. tularensis SchuS4 (Lindgren and Sjostedt, 2016).This method has been performed with Francisella and shows reasonable predictive power of patient outcome when compared to clinical data (Maurin et al, 2000). A more recent method developed by Sutera et al involves a dye uptake assay to quickly and quantitatively measure the susceptibility of intracellular Francisella to extracellular antibiotics.…”
Section: Intracellular Mic Assaymentioning
confidence: 99%
“…As might be predicted, growth of F. tularensis is inhibited by gallium, which competes with ferric iron for uptake and also interferes with iron-dependent biological processes (Olakanmi et al, 2010; Lindgren and Sjöstedt, 2016). Inhibition of the iron-associated enzymes catalase and superoxide dismutase leads to increased susceptibility to oxidative stress (Bakshi et al, 2006; Lindgren et al, 2007; Olakanmi et al, 2010; Binesse et al, 2015).…”
Section: Introductionmentioning
confidence: 97%